Investigations into the production of a harpin elicitor by Pseudomonas syringae pv. syringae isolated from a nectarine tree - Appel, Maryke (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.